Alocação ótima de parques eólicos em sistemas de distribuição considerando incertezas de vento e carga utilizando algorítmo genético - FONSECA, Sebastião Borges (Universidade Federal do Pará, 2017)
This master’s thesis proposes a probabilistic approach to determine the optimal location, sizing and power factor of wind parks in power systems based on Genetic Algorithm. The proposed method considers the intermittent nature of wind and load to minimize the annual energy losses in the system under study. Recent technological advancement has created the opportunity to operate wind parks injecting reactive power into the system, making important to consider different power factor modes. The test system used is a distribution system with 33 buses and the results proved the efficiency of the proposed method and the importance to consider load and wind uncertainties in power system planning.